2019
DOI: 10.1101/721480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivalent and Broad Chromatin Domains Regulate Pro-metastatic Drivers in Melanoma

Abstract: 25Chromatin deregulation is an emerging hallmark of cancer. However, the extent of 26 epigenetic aberrations during tumorigenesis and their relationship with genetic 27 aberrations are poorly understood. Using ChIP-sequencing for enhancers (H3K27ac and 28 H3K4me1), promoters (H3K4me3), active transcription (H3K79me2) and polycomb 29 (H3K27me3) or heterochromatin (H3K9me3) repression we generated chromatin state 30 profiles in metastatic melanoma using 46 tumor samples and cell lines. We identified a 31 strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, Terranova at al. found that metastatic melanomas harbor exceptionally wide H3K4me3 domains [ 119 ]. These domains can span tens of thousands of kilobases, and appear to be involved in the regulation of several EMT transcription factors (POU3F2, SOX9, and PDGFRA) as well as melanocyte-specific master regulators (MITF, ZEB2, and TFAP2A) [ 120 ].…”
Section: Epigenetic Alterations Driving CM Initiation and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Terranova at al. found that metastatic melanomas harbor exceptionally wide H3K4me3 domains [ 119 ]. These domains can span tens of thousands of kilobases, and appear to be involved in the regulation of several EMT transcription factors (POU3F2, SOX9, and PDGFRA) as well as melanocyte-specific master regulators (MITF, ZEB2, and TFAP2A) [ 120 ].…”
Section: Epigenetic Alterations Driving CM Initiation and Progressionmentioning
confidence: 99%
“…These domains can span tens of thousands of kilobases, and appear to be involved in the regulation of several EMT transcription factors (POU3F2, SOX9, and PDGFRA) as well as melanocyte-specific master regulators (MITF, ZEB2, and TFAP2A) [ 120 ]. Terranova et al finally highlighted that particular events such as BRAF or NRAS mutations may employ specific chromatin states (bivalent states and broad H3K4me3 domains) to orchestrate transcriptional changes unique to a genotype, suggesting that epigenetic mechanisms play important roles in regulating CM behaviors [ 119 ].…”
Section: Epigenetic Alterations Driving CM Initiation and Progressionmentioning
confidence: 99%